Using passive acoustic monitoring to investigate the occurrence of cetaceans in a protected marine area in northwest Ireland. (5th January 2020) - Todd, Nicole R.E.; Cronin, Michelle; Luck, Cian; Bennison, Ashley; Jessopp, Mark; Kavanagh, Ailbhe S.
Abstract: Under the EU Habitats Directive, cetacean species must be maintained at favourable conservation status in European waters. Whether this is achieved via protected area designation, curtailment of activities such as fishing or construction, or time restrictions on noise, it is dependent on understanding the temporal patterns in occurrence. Our ability to study this is often limited by the relatively short time-series of data available to researchers. This study uses nine years of passive acoustic monitoring data paired with environmental covariates to better understand the spatio-temporal dynamics of harbour porpoise and dolphin species using generalised estimating equations-generalised linear models (GEE-GLMs). This long-term time-series included periods of increased disturbance due to construction of an underwater gas pipeline in the area, enabling us to investigate the effect of construction on species occurrence. Harbour porpoise and dolphins occurred in every season, with detections peaking in winter. We found a negative association between dolphins and porpoises throughout the year. Inter-annual variation in occurrence was evident, with a cyclical bi-annual pattern highlighted for both species suggesting a complex pattern of movement. Construction activity had a significant negative effect on the presence of porpoise but not dolphins. However, no long-term decrease in detection rates of porpoise was recorded. This study highlights the importance of understanding what factors influence cetacean occurrence as well as the temporal scale of disturbance effects for planning and management of construction activities in coastal areas. Highlights: Long-term passive acoustic monitoring highlights the potential drivers of occurrence in a northeast Atlantic exposed site. Bi-annual pattern of occurrence for cetacean species suggests a more complex movement pattern than previously suggested. We demonstrate a negative effect of construction activity on harbour porpoise occurrence. Spatio-temporal differences in harbour porpoise and dolphins may suggest possible avoidance consistent with previous studies. Winter peak in cetacean occurrence differs to other European regions, highlighting the importance of region-specific studies.